Novel synthetic bisbenzimidazole that targets angiogenesis in Ehrlich ascites carcinoma bearing mice. Issue 12 (15th June 2015) - Roopashree, Rangaswamy; Mohan, Chakrabhavi Dhananjaya; Swaroop, Toreshettahally Ramesh; Jagadish, Swamy; Raghava, Byregowda; Balaji, Kyathegowdanadoddi Srinivas; Jayarama, Shankar; Basappa,; Rangappa, Kanchugarakoppal Subbegowda
Graphical abstract: Abstract: Cancer is a leading cause of death in developed countries and second cause in developing countries. Herein we are reporting the synthesis of novel bisbenzimidazole derivatives and their anticancer properties. Among the newly synthesized bisbenzimidazoles, 3-(4-flurophenylsulfonyl)-1, 7-dimethyl-2-propyl-1 H, 3 H -2, 5-bibenzo[ d ]imidazole (FDPB) presented as a potent antiproliferative agent against HeLa, HCT116 and A549 cells with selectivity over normal Vero cells (IC50 >50 μM). Additionally, we evaluated the efficacy of lead compound against Ehrlich ascites tumor (EAT) bearing mice for its antitumor and antiangiogenic properties. Our lead compound significantly reduced the cell viability, body weight, ascites volume and downregulated the formation of neovasculature and production of Vascular Endothelial Growth Factor (VEGF).